Computed Tomography–Guided Methylene Blue Labeling Prior to Thoracoscopic Resection of Small Deeply Placed Pulmonary Nodules. Do We Really Need Palpation? - Findik, Gokturk; Demiröz, S. Mustafa; Apaydın, Selma Mine Kara; Ertürk, Hakan; Biri, Suzan; Incekara, Funda; Aydogdu, Koray; Kaya, Sadi (The Thoracic and Cardiovascular Surgeon, 2017)
Background Video-assisted thoracic surgery (VATS) is widely used for thoracic surgery operations, and day by day it becomes routine for the excision of undetermined pulmonary nodules. However, it is sometimes hard to reach millimetric nodules through a VATS incision. Therefore, some additional techniques were developed to reach such nodules little in size and which are settled on a challenging localization. In the literature, coils, hook wires, methylene blue, lipidol, and barium staining, and also ultrasound guidance were described for this aim. Herein we discuss our experience with CT-guided methylene blue labeling of small, deeply located pulmonary nodules just before VATS excision.Method From April 2013 to October 2016, 11 patients with millimetric pulmonary nodules (average 8, 7 mm) were evaluated in our clinic. For all these patients who had strong predisposing factors for malignancy, an 18F-FDG PET-CT scan was also performed. The patients whose nodules were decided to be excised were consulted the radiology clinic. The favorable patients were taken to CT room 2 hours prior to the operation, and CT-guided methylene blue staining were performed under sterile conditions.Results Mean nodule size of 11 patients was 8.7 mm (6, 2–12). Mean distance from the visceral pleural surface was 12.7 mm (4–29.3). Four of the nodules were located on the left (2 upper lobes, 2 lower lobes), and seven of them were on the right (four lower lobes, two upper lobes, one middle lobe). The maximum standardized uptake values (SUV max) on 18F-FDG PET/CT scan ranged between 0 and 2, 79.Conclusion CT-guided methylene blue staining of millimetric deeply located pulmonary nodules is a safe and feasible technique that helps surgeon find these undetermined nodules by VATS technique without any need of digital palpation.
Keywords: millimetric pulmonary nodule; video-assisted thoracic surgery; methylene blue; computed tomography–guided localization